Modern gastronomy A to Z : a scientific and gastronomic lexicon - McGee, Harold (CRC Press, 2010)
In A-Z format, this book explains the terminology used in the science of cooking. It also helps readers discover the potential of a wide range of products that can be used in a diversity of preparations.